Experimental problems in the application of UV/visible based methods as the quantification tool for the entrapped/released insulin from PLGA carriers - Lassalle, Verónica Leticia (2009)
Background: Controlled release of medicaments from biodegradable polymers remains the most convenient way for their sustained release. Although a number of articles have been published, experimental work involving the preparation of polymer-based carriers and release procedures are not described with sufficient level of detail to allow other researchers to reproduce the experiments and to compare published results with their own. In this contribution the experimental background of the entrapment and release of insulin from PLGA carriers is described and the problems found at each step related to UV/Visible method used to quantify them are addressed in detail. Results: The quantification of entrapped insulin by UV/visible methods was affected by aggregation. The design of the release experiment influenced the results regarding the entrapment efficiency (EE) and the maximum percentage of released insulin. It was also found that the presence of colloidal polymeric particles, insufficient centrifugation times and the kind of solvent used in the release test might lead to mistakes in the percentage of liberated insulin when UV/visible based methods are employed. Conclusions: This contribution demonstrates that serious discrepancies in the EE and percentage of released protein may arise if some key experimental factors are not taken into account. Therefore, the analysis presented here tries to point out important aspects of this topic currently not reported, unnoticed or not properly analyzed in the open literature. The results are useful for the entrapment of any protein on any polymeric device using UV/visible based methods to quantify them. © 2009 Society of Chemical Industry.